Cultured brain pericytes adopt an immature phenotype and require endothelial cells for expression of canonical markers and ECM genes - Oliveira, Fabiana; Bondareva, Olga; Rodríguez-Aguilera, Jesús Rafael; Sheikh, Bilal N. (Frontiers in Cellular Neuroscience, 2023)
Pericytes (PCs) are essential components of the blood brain barrier. Brain PCs are critical for dynamically regulating blood flow, for maintaining vascular integrity and their dysregulation is associated with a myriad of disorders such as Alzheimer’s disease. To understand their physiological and molecular functions, studies have increasingly focused on primary brain PC isolation and culture. Multiple methods for PC culture have been developed over the years, however, it is still unclear how primary PCs compare to their in vivo counterparts. To address this question, we compared cultured brain PCs at passage 5 and 20 to adult and embryonic brain PCs directly isolated from mouse brains via single cell RNA-seq. Cultured PCs were highly homogeneous, and were most similar to embryonic PCs, while displaying a significantly different transcriptional profile to adult brain PCs. Cultured PCs downregulated canonical PC markers and extracellular matrix (ECM) genes. Importantly, expression of PC markers and ECM genes could be mitigated by co-culture with brain endothelial cells, showing the importance of the endothelium in maintaining PC identity and function. Taken together, these results highlight key transcriptional differences between cultured and in vivo PCs which should be considered when performing in vitro experiments with brain PCs.